2015
DOI: 10.1371/journal.pone.0143171
|View full text |Cite
|
Sign up to set email alerts
|

TRPM8 Channel Activation Induced by Monoterpenoid Rotundifolone Underlies Mesenteric Artery Relaxation

Abstract: In this study, our aims were to investigate transient receptor potential melastatin-8 channels (TRPM8) involvement in rotundifolone induced relaxation in the mesenteric artery and to increase the understanding of the role of these thermosensitive TRP channels in vascular tissue. Thus, message and protein levels of TRPM8 were measured by semi-quantitative PCR and western blotting in superior mesenteric arteries from 12 week-old Spague-Dawley (SD) rats. Isometric tension recordings evaluated the relaxant respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The rising cytosolic calcium concentration induces calmodulin-mediated myosin light chain kinase (MLCK) activation, which results in myosin light chain (MLC) phosphorylation and consequently in VSM contraction and vasoconstriction (Davis and Hill, 1999). This response has been demonstrated in endothelial-denuded vessels (Macpherson et al, 2006;Johnson et al, 2009;Silva et al, 2015), and observed in other smooth muscles, including the bladder (Jun et al, 2012), vas deferens (Boldyrev et al, 2009;Vladymyrova et al, 2011) and gastric fundus (Mustafa and Oriowo, 2005). It has also been proposed that TRPM8 channels might exist in cutaneous sympathetic vasodilator fibers, whereby released acetylcholine could lead to NO-dependent VSM relaxation (Johnson et al, 2009), although no studies have effectively investigated this hypothesis.…”
Section: Menthol Actions On Trpm8 Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rising cytosolic calcium concentration induces calmodulin-mediated myosin light chain kinase (MLCK) activation, which results in myosin light chain (MLC) phosphorylation and consequently in VSM contraction and vasoconstriction (Davis and Hill, 1999). This response has been demonstrated in endothelial-denuded vessels (Macpherson et al, 2006;Johnson et al, 2009;Silva et al, 2015), and observed in other smooth muscles, including the bladder (Jun et al, 2012), vas deferens (Boldyrev et al, 2009;Vladymyrova et al, 2011) and gastric fundus (Mustafa and Oriowo, 2005). It has also been proposed that TRPM8 channels might exist in cutaneous sympathetic vasodilator fibers, whereby released acetylcholine could lead to NO-dependent VSM relaxation (Johnson et al, 2009), although no studies have effectively investigated this hypothesis.…”
Section: Menthol Actions On Trpm8 Channelsmentioning
confidence: 99%
“…The vascular expression of TRPM8 channels seems to differ according to animal species and age, as well as to the type of vascular bed. For example, TRPM8 were identified in rat pudendal (Silva et al, 2015), aortae, tail and mesenteric arteries (Johnson et al, 2009), while another study failed to detect their presence in the mesenteric arteries (Inoue et al, 2006). TRPM8 channels have been detected in different cellular locations, namely the plasma membrane (Gai-ying et al, 2014) and in the membrane of intracellular calcium stores, namely Golgi apparatus (Mahieu et al, 2007) and sarcoplasmic reticulum (SR) (Eccles et al, 1988;Lawrence et al, 2011;Schaefer, 2015), although there are conflicting data regarding the latter (Mahieu et al, 2007).…”
Section: Menthol Actions On Trpm8 Channelsmentioning
confidence: 99%
“…In aorta, mesenteric artery, and femoral artery, TRPM8 activation results in a modest relaxation that is endothelium independent (712). Another study concluded that TRPM8 played a part in mesenteric artery vasodilation in rats, but some of the pharmacological tools used bring the specificity of this conclusion into question (1305). Thus, the role of TRPM8 channels is still relatively unknown.…”
Section: Transient Receptor Potential Channelsmentioning
confidence: 99%
“…Phasic vasorelaxation of mouse mesenteric arteries has previously been associated with the action of agonists of the transient receptor potential melastatin 8 channel (TRPM8, [ 24 , 25 ]) under a similar contractile paradigm. This observation has especial relevance given recent data showing that ±PZQ activates TRPM8 in both heterologous expression experiments, as well as in assays for endogenous TRP activity in dorsal root ganglion neurons [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the efficacy of ( S )-PZQ at causing vasorelaxation ( Fig 2 ), the stereoselectivity of ( S )-PZQ at hTRPM8 ( Fig 3 ) and the proposed role for TRPM8 in mesenteric vascular beds [ 24 , 25 ], secondary assays were performed using single cell confocal Ca 2+ imaging to validate ( S )-PZQ action at human TRPM8. Untransfected, and human TRPM8 transfected, HEK293 cells were challenged with ±PZQ, ( R )-PZQ and ( S )-PZQ and menthol (a TRPM8 agonist).…”
Section: Resultsmentioning
confidence: 99%